(untitled) (Palíndromo, 2013)
This paper deals with some works by Thiago Rocha Pitta, trying to regard two aspects: the fascination in front of the landscape as a disaster; and the interrogation about the visibility of intangible items. Immanuel Kant is present as a theoretical articulator who allows a reflection about the attraction of what is fearful and immeasurable; Maurice Blanchot, whose reflections authorize the understanding of some nuances concerning the creation process; and François Cheng, who suggests the fugacity of vapors through the concept of reciprocal transformation identified with the Chinese landscape painting.